Gaucher's disease - Sezer, Vedat; Çoruh, Mithat (The Turkish Journal of Pediatrics, 1961)
Two cases of Gaucher’s disease are reported, one of them being the acute infantile form and the other apparently the adult type. The first case had no evidence of neurologic symptoms and died under two years of age at home.